Characterization of hair follicle derived stem cells and keratinocytes induction following seeding on chitosan scaffold - Noor, Norhayati Mohd (2016)
Hair follicles repeatedly regress and reconstitute themselves, suggesting the presence of intrinsic tissue stem cells. Adult stem cells isolated from hair follicle have a unique characteristic which is differentiating into keratinocytes. Chitosan skin regenerating template (SRT), produced by AMREC-SIRIM has been successfully used as a scaffold in skin tissue engineering. This study aims to investigate isolation of HFSCs from scalp tissues and the characterization of the stem cells was performed. The HFSCs attachment, growth and differentiation ability on chitosan SRTs were evaluated. HFSCs were isolated from human scalp tissues using cell dissociation method and then cultured in CnT-07 growth media. The squamous shaped HFSCs formed groups of cells and grown well in the CnT-07 growth media. The characterization of the cultured HFSCs was performed by using the stem cell marker of K15 and CD200. HFSCs culture were positive for the presence of K15 and CD200. Meanwhile, the attachment and growth of the HFSCs on the chitosan SRTs were evaluated using scanning electron microscope (SEM), Live/Dead assay and Alamar blue assay. The SEM images revealed that HFSCs were shown to attach and grown on chitosan. A live/dead assay shown that living HFSCs population on chitosan at day 1 was 216±6 meanwhile the dead HFSCs was 99±9 (p=0.068). At day 2, the population of viable HFSCs on the chitosan was 367±18, while the dead population of HFSCs was 213±3 (p=0.068). At day 3, the population of viable HFSCs was 452±18 compared with the dead HFSCs was 221±9 (p=0.068). The population of viable and dead HFSCs grown on chitosan showed no significant differences at day 1, day 2 and day 3. Alamar Blue assay also shown the OD from day 1 to day 7 continues to increase as the days increase, indicating HFSCs able to grow and proliferate on chitosan. The mean of the OD values of HFSCs grown on chitosan on theday 7 was the highest compared to 1, 3, and 5 days of the culture (0.0207 ± 0.001 for day 1; 0.0763 ± 0.003 for day 3; 0.0746 ± 0.003 for day 5; 0.1317 ± 0.020 for day 7). These stem cells were also induced to differentiate into epidermal keratinocytes using CnT-02 differentiation media. The characterization of the epidermal keratinocytes was confirmed by the presence involucrin and K6 positive cells. In this present study, the HFSCs were successfully isolated, grown in CnT-07 growth media and expressing stem cell markers K15 and CD200. The study also proved that the chitosan SRT is suitable for HFSCs to attach, grow and also support the differentiation of HFSCs into epidermal keratinocytes. This study provides knowledge on HFSCs isolation and their growth and differentiation on chitosan that in future can be used as an alternative method in treating burn patients.